SIMBOLOGI AL-QUR’AN: Sebuah Kontribusi untuk Pemetaan Karakter Manusia sebagai Objek Dakwah - Iskandar Mirza (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2008)
The Holy Book (Al-Qur’an) can be made as directive in ekplanatinghuman being character. Al-Qur’an constitute representation of soul ofhuman being and can bge made directive (al-huda), parter (al-furqon)and solution (as-Syifa). One of it’s approach is with seeingcharacteristic simbologi Al-Qur’an. It can be reference to explanatehuman being character.